Entertainment’s impact on shopping behavior in small city malls - Bukhory, Aqmal Aqil (Jurnal Evolusi, 2022)
This qualitative study delves into the intricate relationship between entertainment amenities and shopping behavior within small city malls, focusing on the context of Semenyih, Selangor. This research aims to provide valuable insights for mall managers and retailers seeking to adapt to the evolving needs and behaviors of consumers in these smaller urban centers. Employing qualitative research methods, a series of in-depth interviews were conducted with employers in Semenyih. The sampling strategy utilized a combination of maximum diversity sampling and snowball sampling to ensure a comprehensive representation of perspectives within the local community. The research questions guiding this inquiry revolve around understanding the various roles that entertainment offerings play in shaping shopping behaviors, uncovering the specific challenges encountered by mall managers and retailers in adapting to these changes, and proposing future strategies to enhance the overall shopping experience for local communities. The findings of this study not only shed light on the unique dynamics at play within Semenyih but also offer broader implications for small city malls globally.